Pragmatic Features of Somatic Phraseologies and their Theoretical Significance - M. Batirkhanova (International Journal on Orange Technologies, 2021)
In this article has been illuminated the pragmatic functions of somatic phraseologies in English and Uzbek languages. Pragmatic functions of the phraseological units of modern English, its history and development paths, as well as different types of phraseological units. One of the most debatable problems in modern phraseology is the problem of functioning of phraseological units (PU). The results of studying the basic pragmatic functions of phraseological units in modern English are provided in this paper.